2010
DOI: 10.1016/j.devcel.2010.03.008
|View full text |Cite
|
Sign up to set email alerts
|

FoxOs Inhibit mTORC1 and Activate Akt by Inducing the Expression of Sestrin3 and Rictor

Abstract: Summary FoxO transcription factors and TORC1 are conserved downstream effectors of Akt. Here we unraveled regulatory circuits underlying interplay between Akt, FoxO, and mTOR. Activated FoxO1 inhibits mTORC1 by TSC2-dependent and TSC2-independent mechanisms. First, FoxO1 binds the promoter region of Sestrin3 (Sesn3) gene and directly elevates Sesn3 expression, which in turn inhibits mTORC1 activity in Tsc2-proficient cells. Second, FoxO1 elevates the expression of Rictor leading to increased mTORC2 activity th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
286
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 319 publications
(306 citation statements)
references
References 39 publications
19
286
1
Order By: Relevance
“…Subsequent Affymetrix profiling of a time series of FOXR1 knockdown combined with transcription factor binding site enrichment analysis revealed that many putative and known forkhead-box target genes were upregulated following FOXR1 knockdown. Among them were the well-known FOXO target genes p27Kip1, p21Cip1 and Rictor (Stahl et al, 2002;Gomis et al, 2006;Chen et al, 2010). This strongly indicated that FOXO transcription factors may have been activated following FOXR1 knockdown.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Subsequent Affymetrix profiling of a time series of FOXR1 knockdown combined with transcription factor binding site enrichment analysis revealed that many putative and known forkhead-box target genes were upregulated following FOXR1 knockdown. Among them were the well-known FOXO target genes p27Kip1, p21Cip1 and Rictor (Stahl et al, 2002;Gomis et al, 2006;Chen et al, 2010). This strongly indicated that FOXO transcription factors may have been activated following FOXR1 knockdown.…”
Section: Discussionmentioning
confidence: 90%
“…Interestingly, these three genes are well-characterized FOXO family target genes normally upregulated by FOXO activity (Stahl et al, 2002;Gomis et al, 2006;Chen et al, 2010). This finding raised the possibility that forkhead-box transcription factors and particularly the FOXO family of transcription factors were inactivated by FOXR1 and re-activated upon FOXR1 silencing.…”
Section: Foxr1 Suppresses Forkhead-box Family Target Genesmentioning
confidence: 99%
“…Mechanistically, our survey of genes in mTORC1 pathway confirmed that SESN3 and RICTOR, bona fide transcriptional targets of FOXO, were significantly downregulated in KO brains (Figure 5a,b). Previous in vitro studies also support effector role of SESN3 and RICTOR in FOXO‐regulated mTORC1 and AKT activity, respectively (Chen et al., 2010). Indeed, reduction of SESN3 expression was well correlated with increased phosphorylation of S6K1 and 4EBP1 in KO brains (Figure 5a,b).…”
Section: Resultsmentioning
confidence: 99%
“…Similarly to Sesn2, Sesn3 has been shown to inhibit mTOR complex 1 (mTORC1), and Akt affects Sesn3 expression through FoxO1. 18 We analyzed Sesn3 expression in response to Figure S3A). The downregulation of Sesn2 had no effect on mTOR activity in basal conditions and did not affect the inhibition of mTOR by rapamycin.…”
Section: Resultsmentioning
confidence: 99%